2022
DOI: 10.1029/2021gl095996
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Imaging of Glacier Structures at High‐Resolution Using Source Localization With a Dense Seismic Array

Abstract: Dense seismic array monitoring combined with advanced processing can help retrieve and locate a variety of seismic sources with unprecedented resolution and spatial coverage. We present a methodology that goes beyond classical localization algorithms through gathering various types of sources (impulsive or continuous) using a single scheme based on a gradient‐descent optimization and evaluating different levels of phase coherence. We apply our methodology on an Alpine glacier and demonstrate that we can retrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 47 publications
0
24
0
Order By: Relevance
“…We extracted information from an extensive beamforming catalog which was developed using an advanced MFP localization scheme based on a gradient‐decent optimization that meets the challenging, seismically “loud” environment. A complete detailed description on the methodology and the MFP implementation can be found in (Nanni et al., 2022). We used four sub‐catalogs with center frequencies of 5, 10, 15, and 20 Hz.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We extracted information from an extensive beamforming catalog which was developed using an advanced MFP localization scheme based on a gradient‐decent optimization that meets the challenging, seismically “loud” environment. A complete detailed description on the methodology and the MFP implementation can be found in (Nanni et al., 2022). We used four sub‐catalogs with center frequencies of 5, 10, 15, and 20 Hz.…”
Section: Methodsmentioning
confidence: 99%
“…Matched field processing (MFP) is the natural extension of plane wave beamforming and yields for the location of seismic noise sources in range, depth and azimuth by analyzing spherical waves in the close environment of the underlying seismic array (Bucker, 1976). The approach was originally developed in ocean acoustics (Baggeroer et al, 1993;Kuperman & Turek, 1997), but a broad spectrum of applications can be found in environmental seismology to study near-surface processes on the exploration scale (Corciulo et al, 2012;Cros et al, 2011;Umlauft & Korn, 2019;Vandemeulebrouck et al, 2010) and the rapidly emerging special research field of cryoseismology to better understand dynamics within for example, Alpine glacial ice (Nanni et al, 2021(Nanni et al, , 2022Umlauft et al, 2021;Walter et al, 2015Walter et al, , 2020.…”
Section: Matched Field Processingmentioning
confidence: 99%
“…Matched field processing (MFP) is the natural extension of plane wave beamforming and yields for the location of seismic noise sources in range, depth and azimuth by analysing spherical waves in the close environment of the underlying seismic array [45]. The approach was originally developed in ocean acoustics [46,47], but a broad spectrum of applications can be found in environmental seismology to study near-surface processes on the exploration scale [48,49,50,51] and the rapidly emerging special research field of cryoseismology to better understand dynamics within e.g., Alpine glacial ice [52,22,27,53,54].…”
Section: Matched Field Processingmentioning
confidence: 99%
“…We extracted information from an extensive beamforming catalog which was developed using an advanced matched field processing localization scheme based on a gradient-decent optimization that meets the challenging, seismically "loud" environment. A complete detailed description on the methodology and the MFP implementation can be found in [54]. We used four sub-catalogues with center frequencies of 5 Hz, 10 Hz, 15 Hz and 20 Hz.…”
Section: Data Featuresmentioning
confidence: 99%
See 1 more Smart Citation